Survival and risk factors among upper tract urothelial carcinoma patients after radical nephroureterectomy in Northeast China - Gao, Jianing; Liu, Jingya; Liu, Jianyu; Lin, Shiyan; Ding, Dexin (Frontiers in Oncology, 2022)
Objective: The study objective was to investigate the prognostic risk factors related to overall survival (OS), cancer-specific survival (CSS), recurrence-free survival (RFS), and metastasis-free survival (MFS) after radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC). Patients were then divided into different risk groups (based on their number of prognostic risk factors), and specific postoperative treatment plans were formulated for patients in different risk groups. Methods: We retrospectively analyzed the data of 401 patients with UTUC who underwent RNU between 2010 and 2020. Univariate and multivariate Cox regression analyses were used to evaluate the associations of clinicopathological variables with prognosis among UTUC patients. Kaplan–Meier survival analysis of patients in different risk groups (based on their the number of prognostic risk factors) was conducted. Results: Multivariate Cox regression analysis showed that sex (being male), LVI, pT stage (>pT2), and lack of postoperative intravesical instillation were independent risk predictors of shorter OS,CSS, RFS, and MFS (all P<0.05). Laparoscopic RNU was also associated with shorter OS, CSS, and MFS, but not with shorter RFS (P=0.068). After risk stratification, the 5-year OS, CSS, RFS, and MFS in the high-risk group were 42.3%, 46.4%, 41%, and 46%, respectively. Conclusions: Sex (being male), LVI, pT stage (>pT2), and intravesical instillation were independent predictors of OS, CSS, RFS, and MFS for UTUC. All were risk factors, except for intravesical instillation, which was a protective factor. Additionally, laparoscopic RNU was an independent risk factor for OS, CSS, and MFS. Patients in the high-risk group may benefit greatly from adjuvant or neoadjuvant chemotherapy.